Lexical semantic fields on textbook for reading course in Universitas Negeri Malang - Nurhidayati Nurhidayati; Kholisin Kholisin; Irhamni Irhamni; Mohd Azidan bin Abdul Jabar; Dzulfikri Dzulfikri (Fakultas Sastra Universitas Negeri Malang, 2023)
This study aims to describe the lexical semantic fields of reading textbooks in Universitas Negeri Malang, specifically in categories being, cosmic, energetic, substantial, terrestrial, objective, living, animate, and human. It used a descriptive qualitative method with a semantic analysis approach. The semantic approach was selected since we intended to comprehend the semantic phenomenon from the lexical-semantic field aspect of a specific textbook course. In detail, we started the research by describing the lexical-semantic field in the textbook and classified the words and phrases. Further, we identified the rational understanding of those words and phrases as a complete understanding of a word requires comprehending the connection with the surrounding words, known as the semantic field. The interconnection of words’ meanings is caused by their specific meaning in particular social situation and condition. Our analysis results suggested that the lexical-semantic field in the reading course textbook (Al-Arabiyah Baina Yadaika chapter 1) from Universitas Negeri Malang is dominated by the being and human semantic fields. Accordingly, the lecturers are suggested to complete the reading textbook with more contextual materials with different semantic fields following students’ interests.Keywords: semantic field, lexical, learning material, readingMedan makna leksikal dalam bahan ajar matakuliah membaca di Universitas Negeri MalangTujuan dari penelitian adalah untuk mendeskripsikan medan makna leksikal dalam bahan ajar matakuliah membaca di Universitas Negeri Malang pada kategori being, cosmic, energetic, substancial, terrestrial, objective, living, animate, dan human. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan menggunakan pendekatan analisis semantik. Pendekatan semantik digunakan karena kami berupaya memahami fenomena semantik dari sisi medan makna leksikal yang terdapat pada bahan ajar matakuliah tertentu. Secara rinci, kami memulai penelitian dengan mendeskripsikan bidang leksikal-semantik dalam buku teks dan mengklasifikasikan kata dan frasa. Selanjutnya, kami mengidentifikasi pemahaman rasional dari kata-kata dan frase tersebut karena pemahaman yang lengkap dari sebuah kata memerlukan pemahaman hubungan dengan kata-kata sekitarnya, yang dikenal sebagai bidang semantik. Keterkaitan makna kata-kata disebabkan oleh maknanya yang spesifik dalam situasi dan kondisi sosial tertentu. Hasil analisis kami menunjukkan bahwa bidang leksikal-semantik dalam buku teks mata kuliah membaca (Al-Arabiyah Baina Yadaika bab 1) dari Universitas Negeri Malang didominasi oleh bidang semantik makhluk (being) dan manusia (human). Oleh karena itu, disarankan kepada dosen untuk melengkapi buku teks bacaan dengan materi yang lebih kontekstual dengan bidang semantik yang bervariasi medan maknanya sesuai dengan minat mahasiswa.Kata kunci: medan makna, leksikal, materi pembelajaran, membaca